Ruins of Paper: Dickens and the Necropolitan Library - Stauffer, Andrew (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractIn his journalism and novels (particularly Bleak House and Our Mutual Friend), Charles Dickens presents London as a writer’s necropolis, a city of disintegrating paper and dead letters, a failed archival space. This essay examines a nexus of images in Dickens’ work – involving dust, Egyptian ruins and mummies, and paper – as revealing characteristic Victorian concerns regarding the changing status of paper and the archive. With reference to developments in papermaking technologies and the beginnings of Egyptian archaeology, I demonstrate some of the ways that nineteenth-century authors were newly troubled by the archival as such. Dickens is particularly haunted by an urban vision of paper as everywhere and everywhere turning into blank, wasting forms. I connect this phenomenon to the British reception of the material legacies of ancient Egypt, particularly the mummified dead. The Victorian era was the great age of paper, as technological developments transformed the industry and multiplied its productivity many times over. Read in the context of these changes, and in relation to Egyptology (that other burgeoning industry of records and remains), the work of Dickens reflects deep anxieties regarding the whelming flood of precariously fragile paper—anxieties that have a center in the necropolitan library.